Use of restaurant food profits in nilotic tilapia feeding: Aproveitamento de resíduos alimentares de restaurante na alimentação de tilápia nilótica - Deminicis, Bruno Borges; Mendonça, Pedro Pierro (Scientia Agraria Paranaensis, 2022)
Aquaculture is the fastest growing sector in food production, however spending on feed, which can reach up to 80% of the total cost of production. In an attempt to solve this problem, one of the options would be to substitute traditional ingredients for alternatives, in an attempt to minimize the final cost of the feed. Thus, the objective of this work was to evaluate levels of inclusion of restaurant waste in the productive performance, in Nile tilapia, for this purpose 300 juveniles were used. The animals were distributed in 10 boxes of 500 L, being interconnected in a water recirculation system, with an average of two liters of water per minute, using a biological filter for mineralization of ammonia in nitrite, and of nitrite in nitrate and a system continuous aeration with “microporous” stones connected to a portable air compressor. The experimental design used was completely randomized, with four treatments, with performance with five replications and digestibility with three. The treatments consisted of four isoproteic and isoenergetic diets, with different levels of inclusion of the restaurant meal bran (0, 5, 10 and 15%). The physical-chemical parameters of the water, such as dissolved oxygen, pH and temperature were analyzed throughout the experimental period, monitored every two days. The fish were subjected to a 12-hour photoperiod followed by light. At the end of the experimental period, the animals were fasted for 24 hours, then sacrificed by thermal shock with ice and subsequently submitted to biometry. The inclusion of restaurant waste bran at different levels did not negatively affect the performance of the animals, up to 45 days of age.